Case report: A rare case of skin abscess caused by coinfection of Actinobaculum schaalii and Actinomyces turicensis - Liu, Peng; Sun, Kangchao; Li, Rongguo; Chen, Xiaodi (Frontiers in Cellular and Infection Microbiology, 2024)
Skin abscess is one of the most common infections of the skin and soft tissues. However, anaerobic bacteria are infrequently identified as the causative agents of this particular form of abscess. In this case, a 34-year-old pregnant woman was diagnosed with a skin abscess with the use of ultrasonography. The microbiological analysis results of the purulent fluid revealed the coinfection of Actinobaculum schaalii and Actinomyces turicensis. The patient was first treated empirically with 3 days of cefathiamidine, which resulted in no symptom improvement. Subsequently, a surgical procedure involving incision and draining was performed, with the administration of ceftriaxone. After 7 days of antibiotic intervention, the patient exhibited a satisfactory recovery. Clinicians need to be aware of other types of infections that might be attributed to Actinobaculum schaalii and Actinomyces turicensis, in addition to urinary tract infections.